2006
DOI: 10.1017/s0022215106001290
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing training opportunities for otolaryngology senior house officers: an audit

Abstract: Implementation of the European Working Time Directive and the Modernising Medical Careers initiative will mean junior surgeons must be trained in fewer hours over a shorter period. For this reason, junior surgeon training opportunities must be optimized. We undertook a departmental audit to identify where opportunities to train senior house officers (SHOs) in theatre were being lost, so that appropriate timetable changes could be made in order to optimize exposure to suitable surgical cases. During the first a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Implementation of the European Working Time Directive and the ‘Modernising Medical Careers’ initiative will mean that junior surgeons must be trained in fewer hours over a shorter period; for this reason, surgical training opportunities must be optimised 9 . The continued reduction in UK junior doctors’ hours has made it no longer appropriate to assume that all activities represent either training or service individually in relation to a trainee's learning curves 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of the European Working Time Directive and the ‘Modernising Medical Careers’ initiative will mean that junior surgeons must be trained in fewer hours over a shorter period; for this reason, surgical training opportunities must be optimised 9 . The continued reduction in UK junior doctors’ hours has made it no longer appropriate to assume that all activities represent either training or service individually in relation to a trainee's learning curves 10 .…”
Section: Discussionmentioning
confidence: 99%
“…A solution may be altering rotas to emphasise clinic or theatre time, 3 benefiting both those intent on a career in ENT and those with little specific interest.…”
Section: Discussionmentioning
confidence: 99%
“…The actual number of operations carried out per trainee may be far less than the numbers of operations available per trainee calculated in this study for a number of reasons, including the availability of an appropriate trainer, lack of training time and pressures from other service and training commitments. This is illustrated by an audit 2006 by Wasson et al , 17 which found that SHOs in otolaryngology participated in only 27% of the available number of operative cases. With the increasing use of online electronic logbooks, it may become possible to measure trainees’ actual operative activity.…”
Section: Discussionmentioning
confidence: 99%